2015
DOI: 10.18178/ijmmm.2016.4.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Charpy Impact Resistances of Carbon Nanotubes Reinforced High Density Polyethylene Nanocomposite Materials

Abstract: Abstract-In this study, Multiwall Carbon Nanotubes (MWCNT) reinforced High Density Polyethylene (HDPE) materials were used. Mechanical properties of the samples reinforced with Carbon Nanotubes at weight ratios of 1%, 3% and 5% were investigated. Reinforced samples were compared to samples produced with pure High density Polyethylene. Samples were produced by plastic injection method. The samples were then subjected to experiments and impact resistance values were measured in accordance with ASTM D6110 standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…CNT have gained a huge attention in various fields such as biomedical 17 and electrical 18 owing to their unique structure of tube-shaped allotropes of carbon with ultra-high aspect ratio, 19 remarkable mechanical and electronic properties. 20 For instance, by adding 0.1-2.0 wt% of multiwalled carbon nanotubes (MWCNT) into PP, the mechanical and viscosity properties of the nanocomposites were improved. 15 Fouad et al, 21 has investigated the HDPE/CNT nanocomposites prepared via extrusion blending technique and the findings reported that 4 wt% of carbon nanoparticles to improve storage and Young's modulus and yield strength without affect the melting temperature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…CNT have gained a huge attention in various fields such as biomedical 17 and electrical 18 owing to their unique structure of tube-shaped allotropes of carbon with ultra-high aspect ratio, 19 remarkable mechanical and electronic properties. 20 For instance, by adding 0.1-2.0 wt% of multiwalled carbon nanotubes (MWCNT) into PP, the mechanical and viscosity properties of the nanocomposites were improved. 15 Fouad et al, 21 has investigated the HDPE/CNT nanocomposites prepared via extrusion blending technique and the findings reported that 4 wt% of carbon nanoparticles to improve storage and Young's modulus and yield strength without affect the melting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…29 In another study of hybrid CNT/clay nanofillers on immiscible PE/PP blend, the finding reported the selective localization of CNT within the PE phase, while the clay particles showed affinity towards the PP phase, however due to the poor adhesion between PP matrix and the clay, the mechanical properties were degraded. 30 Numerous literatures showed the investigation on single polyolefin incorporated with CNT or nanoclay, 9,10,20,31,32 yet the research work published on polymer blend based nanocomposites without compatibilizer is limited. Based on the recent works by our research group, the rHDPE/rPET blend was used as matrix to incorporate with nanoclay and the focus was placed on the processing parameter factors such as the mixing methods, temperature, and rotation speed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Abenojar et al modified the epoxy matrix with B 4 C and reported an excellent potential for enhancing of strength. 7 Furthermore, some researchers have preferred the MWCNT, 3,[8][9][10][11][12][13][14] nano or micro fibers or ceramic particles and they have obtained positive results. [15][16][17][18][19] Guo et al stated that well dispersion of MWCNT in the epoxy has a positive effect on the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%